Causes of morbilliform rash in a highly immunised English population. Issue 3 (1st September 2002) - Ramsay, M; Reacher, M; O'Flynn, C; Buttery, R; Hadden, F; Cohen, B; Knowles, W; Wreghitt, T; Brown, D
Abstract : Aims: To determine the causes of morbilliform rash and fever in a population with high vaccination coverage for measles and rubella. Methods: Comprehensive laboratory investigation additional to routine oral fluid testing of children presenting to primary care physicians in East Anglia, England. Results: Laboratory confirmation of infection was obtained in 93 (48%) of 195 children: parvovirus B19 in 34 (17%); group A streptococcus in 30 (15%); human herpesvirus type 6 in 11 (6%); enterovirus in nine (5%); adenovirus in seven (4%); and group C streptococcus in six (3%) (four individuals tested positive for two agents). None had measles or rubella. Conclusions: Oral fluid testing to cover infections additional to measles and rubella aids clinical management and is likely to maintain uptake of testing, which is essential for measles and rubella surveillance in highly immunised low incidence populations.